2022
DOI: 10.3389/fphys.2022.984305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an experimental short-time high-intensity warm-up on explosive muscle strength performance in soccer players: A pilot study

Abstract: Objective: This study aimed to evaluate the effects of an experimental short-time warm-up consisting of a small number of intermittent high-intensity sprints on explosive muscle strength performance in soccer players and to identify recovery times after performing the sprints. Furthermore, we evaluated the reliability of a smartphone app in jumping performance.Methods: Twenty male soccer players were given the following tests: 1) the counter-movement jump (CMJ) test with the Microgate system, 2) the counter-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Due to its paramount importance in team sports as well as track and field, a vast amount of research was performed to ascertain training routines to improve jumping and sprinting performance ( Ramirez-Campillo et al, 2020 ; Byrne et al, 2022 ; Patti et al, 2022 ; Ramirez-Campillo et al, 2022 ). Indeed, authors described speed strength to be game-changing in soccer ( Requena et al, 2014 ; Keiner et al, 2022b ), basketball ( Brughelli et al, 2008 ; Delextrat and Cohen, 2008 ; Delextrat and Cohen, 2009 ), or handball ( Manchado et al, 2013 ; Wagner et al, 2014 ), underlining the relevance of developing appropriate and effective training routines.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its paramount importance in team sports as well as track and field, a vast amount of research was performed to ascertain training routines to improve jumping and sprinting performance ( Ramirez-Campillo et al, 2020 ; Byrne et al, 2022 ; Patti et al, 2022 ; Ramirez-Campillo et al, 2022 ). Indeed, authors described speed strength to be game-changing in soccer ( Requena et al, 2014 ; Keiner et al, 2022b ), basketball ( Brughelli et al, 2008 ; Delextrat and Cohen, 2008 ; Delextrat and Cohen, 2009 ), or handball ( Manchado et al, 2013 ; Wagner et al, 2014 ), underlining the relevance of developing appropriate and effective training routines.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, another recent study aimed to identify recovery times after performing the sprints, evaluated the effects of an experimental short-time warm-up consisting of a small number of intermittent high-intensity sprints (three maximum sprints over 60 m with 120 s of recovery between sprints) on explosive muscle strength performance in soccer players [ 19 ]. The data indicated that only 330 s (5 min and 30 s) after the last sprint, the countermovement jump performance recovered to baseline levels [ 19 ]. These results are in line with another study documenting that performance was optimal with recovery times between 7 and 10 min for intensities between 60 and 85% of 1RM [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior each series of penalty kicks, the participants performed a self-selected warm-up, lasting approximately 15 min, and three penalty kicks as familiarization (one penalty kick for each target goal, i.e., right, center, left indicated through the experimenter's verbal commands). Since it is known that warm-up could affect performance [ 40 , 41 ], the self-selected warm-up was their usual warm-up and was the same for all participants. In fact, all participants belonged to the same team and their coach, who was present throughout the experimental protocol, conducted the warm-up which included light jogging followed by dynamic lower extremity movements and joint mobility exercises.…”
Section: Methodsmentioning
confidence: 99%